High pressure fosters protein refolding from aggregates at high concentrations - St. John, Richard J. (The National Academy of Sciences, 1999)
High hydrostatic pressures (1–2 kbar), combined with low, nondenaturing concentrations of guanidine hydrochloride (GdmHCl) foster disaggregation and refolding of denatured and aggregated human growth hormone and lysozyme, and β-lactamase inclusion bodies. One hundred percent recovery of properly folded protein can be obtained by applying pressures of 2 kbar to suspensions containing aggregates of recombinant human growth hormone (up to 8.7 mg/ml) and 0.75 M GdmHCl. Covalently crosslinked, insoluble aggregates of lysozyme could be refolded to native, functional protein at a 70% yield, independent of protein concentration up to 2 mg/ml. Inclusion bodies containing β-lactamase could be refolded at high yields of active protein, even without added GdmHCl.